2023
DOI: 10.1097/eja.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative recovery after breast cancer surgery

Abstract: BACKGROUND Perioperative use of opioids has revealed significant adverse effects associated with poor postoperative outcomes. OBJECTIVE To determine whether opioid-free anaesthesia based on thoracic paravertebral block (TPVB) could improve postoperative recovery after breast cancer surgery. DESIGN A randomised controlled trial. SETTING A tertiary teaching hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…An interesting debate has followed the publication in the journal of a recent editorial and two randomised controlled trials (RCTs) on opioid-free anaesthesia (OFA) 1–3 …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…An interesting debate has followed the publication in the journal of a recent editorial and two randomised controlled trials (RCTs) on opioid-free anaesthesia (OFA) 1–3 …”
mentioning
confidence: 99%
“…In the same issue, Zhou et al described a large RCT in endoscopic sinus surgery and concluded that OFA can be an alternative to opioid-based anaesthesia (OBA) 2 . They used a quality of life questionnaire (QoR-40) as primary outcome measure, as did Zhang et al 3 (QoR-15), concluding, in the same issue, that OFA with thoracic paravertebral block improved early quality of recovery when compared with OBA.…”
mentioning
confidence: 99%
See 2 more Smart Citations